Deviance and Social Control - Boeri, Miriam (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
This course serves to provide a survey of the nature, causes, and consequences of deviant behavior; provide an analysis of the problems of definition, identification, explanation, and social reaction to violations of institutional expectations; present techniques of social control. OBJECTIVES: What do we mean by deviance? What is social control? How is deviant behavior socially controlled? Who is deviant and who controls? My objective in this class is to help students gain an understanding of the major explanations, theories, and sociological research on deviance and social control. The textbook and readings will provide a general overview of sociological theories and examples of deviant behavior. Field trips, journal articles, movies, and online discussions will allow students to read, observe, and discuss examples of behavior considered a "violation of cultural norms." My goal is that each student leaves this class with an intellectual, sociological, and practical understanding of deviance and social control.